Cryptic diversity revealed by DNA barcoding in Colombian illegally traded bird species - Mendoza, Ángela María (2016)
Colombia is the country with the largest number of bird species worldwide, yet its avifauna is seriously threatened by habitat degradation and poaching. We built a DNA barcode library of nearly half of the bird species listed in the CITES appendices for Colombia, thereby constructing a species identification reference that will help in global efforts for controlling illegal species trade. We obtained the COI barcode sequence of 151 species based on 281 samples, representing 46% of CITES bird species registered for Colombia. The species analysed belong to nine families, where Trochilidae and Psittacidae are the most abundant ones. We sequenced for the first time the DNA barcode of 47 species, mainly hummingbirds endemic of the Northern Andes region. We found a correct match between morphological and genetic identification for 86–92% of the species analysed, depending on the cluster analysis performed (BIN, ABGD and TaxonDNA). Additionally, we identified eleven cases of high intraspecific divergence based on K2P genetic distances (up to 14.61%) that could reflect cryptic diversity. In these cases, the specimens were collected in geographically distant sites such as different mountain systems, opposite flanks of the mountain or different elevations. Likewise, we found two cases of possible hybridization and incomplete lineage sorting. This survey constitutes the first attempt to build the DNA barcode library of endangered bird species in Colombia establishing as a reference for management programs of illegal species trade, and providing major insights of phylogeographic structure that can guide future taxonomic research.